2019
DOI: 10.1292/jvms.18-0421
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of atypical <i>Actinobacillus pleuropneumoniae</i> serovar 15 lacking the <i>apxIICA</i> genes in Japan

Abstract: Six atypical Actinobacillus pleuropneumoniae serovar 15 strains were isolated from pneumonic lesions of naturally infected dead pigs from the same farm in Japan. Genetic analyses of apx genes revealed that the atypical isolates contained the toxin-associated genes apxIBD, apxIIICA, apxIIIBD, and apxIVA, but not apxIICA. Coinciding with the result of the atypical gene profile, analyses of toxin pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…As a consequence of the repeatedly reported detection of atypical isolates in A. pleuropneumoniae [ 17 21 ], an additional aim of this study was the characterization of the apx -profiles in order to check the validity of the alleged serovar-specific association of these toxin genes. Among others, strains with atypical toxin gene profiles were found in Switzerland, Korea, Japan and Australia, belonging to a wide range of different serovars [ 17 21 ]. The toxin typing performed here revealed that only 7% of the examined isolates deviated from the expected apx -profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of the repeatedly reported detection of atypical isolates in A. pleuropneumoniae [ 17 21 ], an additional aim of this study was the characterization of the apx -profiles in order to check the validity of the alleged serovar-specific association of these toxin genes. Among others, strains with atypical toxin gene profiles were found in Switzerland, Korea, Japan and Australia, belonging to a wide range of different serovars [ 17 21 ]. The toxin typing performed here revealed that only 7% of the examined isolates deviated from the expected apx -profile.…”
Section: Discussionmentioning
confidence: 99%
“…The description of the serovar-specific production of Apx toxins dates back to the 1990s. Since then, however, reports of atypical isolates of the bacterium have been published repeatedly [ 17 21 ] but the relevance of these findings is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Serovars carrying apxIII together with apxII are serovars 2, 4, 6, 8, and 15; they are also considered virulent, i.e., traditionally, high virulence is attributed to the presence of at least two secreted exotoxins (ApxII plus ApxI or ApxIII) besides the intrinsically produced ApxIV, while biotypes/serovars carrying only one toxin gene besides ApxIV are considered to show low virulence, thus they are unlikely to cause epizootics [ 3 ]. In addition to typical toxin-producing strains, atypical ones lacking certain genes also occur [ 26 ]. This virulence-based grouping is in line with the lipopolysaccharide O-chain or omlA phylogroups as well [ 3 , 27 ]; however, other virulence factors also contribute to disease severity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further examination of the genes for the expression, activation, and secretion of Apx toxins by PCR 1,17 revealed that these 2 isolates of A. pleuropneumoniae , named IB19-1 and IB19-2, contained the same apx gene combination as serovars 2, 4, 6, 8, and 15 (an apxIICA, apxIIICA, apxIBD, apxIIIBD , and apxIVA gene pattern). The serovar 15 reference strain HS143 1 and 3 representative field isolates (A–C) 14 of serovar 15 isolated from different geographic regions in Japan were used in the further characterization of these isolates as described below.…”
mentioning
confidence: 99%
“…Template DNA was prepared as described previously. 14 Briefly, the conditions for PCR were as follows: 94°C for 1 min (1 cycle), 98°C for 10 s, and 68°C for 3 min 30 s (30 cycles). The PCR products were purified (NucleoSpin gel, PCR clean - up kit; Macherey-Nagel), and the nucleotide sequences were determined using a primer-walking procedure as described previously.…”
mentioning
confidence: 99%